2020
DOI: 10.1016/s2665-9913(20)30168-5
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated and patient-specific immune cell signatures in juvenile-onset systemic lupus erythematosus: patient stratification using a machine-learning approach

Abstract: Background Juvenile-onset systemic lupus erythematosus (SLE) is a rare autoimmune rheumatic disease characterised by more severe disease manifestations, earlier damage accrual, and higher mortality than in adult-onset SLE. We aimed to use machine-learning approaches to characterise the immune cell profile of patients with juvenile-onset SLE and investigate links with the disease trajectory over time. Methods This study included patients who attended the University College London Hospital (London, UK) adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 33 publications
9
46
2
Order By: Relevance
“…As a data-driven method, the Forest-based Classification and Regression tool performs better with large datasets [at least several hundred input analysis units according to the method guidance provided by the software producer (68), while in our study, we used 71 districts for model training and 151 districts for prediction]. However, some studies have reported successful implementation of this approach on relatively small datasets (69,70). Increased number of trees (1,000 in our study) allows reducing out-of-bag errors, which represent portions of data not participating in trees' construction.…”
Section: Discussionmentioning
confidence: 99%
“…As a data-driven method, the Forest-based Classification and Regression tool performs better with large datasets [at least several hundred input analysis units according to the method guidance provided by the software producer (68), while in our study, we used 71 districts for model training and 151 districts for prediction]. However, some studies have reported successful implementation of this approach on relatively small datasets (69,70). Increased number of trees (1,000 in our study) allows reducing out-of-bag errors, which represent portions of data not participating in trees' construction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PID, immunophenotyping of B and T cells in SLE and other autoimmune diseases is mainly used in scientific research and clinical trials [ 27 ]. Therefore, physicians are not familiar with the interpretation and utility of lymphocyte subset counts in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the use of high-throughput technologies has enabled the development of computational methods for the processing of patient omic data in search of novel and more precise conclusions [5052]. For instance, the implementation of machine learning algorithms in high-dimensional data analysis has previously been used to improve stratification of patients [5355] or to predict disease activity [56,57] in RA and SLE. In our study, we have used DNA methylation in addition to clinical data of UA patients by applying machine learning approaches, fine-tuning the prediction performance of previously existing classifiers [3] in an independent validation cohort.…”
Section: Discussionmentioning
confidence: 99%